FAMILY CARE GIVER PADA KELUARGA PENDERITA HIPERTENSI DENGAN TERAPI KOMPLEMENTER (BAHAN HERBAL) DI KELOMPOK DASAWISMA 2 DESA TLOBONG - Silvitasari, Ika (P3M STIKES Aisyiyah Surakarta, 2018)
Complementary therapy with herbal ingredients in hypertensive patients is widelyused by society in general. This therapy has no harmful side effects, is easy to use and does notcost much. Target and output: homeless and dasa wisma cadres who have family members withhypertension capable of performing hypertension treatment in family members suffering fromhypertension. Method of implementation: provide health counseling by using lecture methodusing media LCD, Liflet, and practice about hypertension, herbal compound material therapy forhypertension and blood pressure measurement. Thank you very much. Results and conclusions:Blood pressure decreased by an average of 10-20 mmHg in five family members with hypertension.Families can provide complementary therapy of herbal ingredients as hypertension therapy.